Sertifikasi Halal di MUI Lampung Pasca Undang -Undang Nomor 34 Tahun 2014 Serta Problematika UMKM - Aliyudin Aliyudin; Khoirul Abror; Khairuddin Khairuddin; Abdurrahman Hilabi (Prodi Perbankan Syariah FAI UMT, 2022)
This research was conducted by focusing on the problem; what is the obligation for halal certification before and before the enactment of Law No. 34 of 2014?, how is the implementation of halal product certification by an institution that is proven in this case BPJPH?, and what is the role of MUI in implementing halal certification?, obstacles and legal impacts of halal certification obligations?. This research is a normative juridical research with qualitative descriptive method. As a result, MUI has the right to issue Halal letters, which is the basis for issuing halal certificates by BPJPH, besides that MUI has other functions regulated by law which at the same time strengthens the legitimacy of halal certificates. The impact is that halal certificates provide added value for UMKM products, but the costs and socialization that are still minimal are an obstacle for UMKM that are still developing